StockOptions a neural network prediction system for the Philippine stock market - Cruz, Mary Ann G. (1998)
The Philippine Stock Market is characterized by its randomness. Actual price fluctuations whether up or down, cannot be predicted - a picture of absolute chaos. Many techniques have been devised to help bring some level of predictability to the market. Stocks are pieces of paper that represent ownership in corporations. Stocks are frequently traded, hopefully sold at a higher price than for what they were originally purchased. The stock market is where the prices of firms' stocks are set and trades are made. How these trades affect the prices, no one truly knows. Stock market prices are not constant and may undergo violent upheavals or gradual slides. Despite this inherent unpredictability, market players are not at a complete loss. Methods of analysis have been devised and refined through years, but they are not easy to learn and difficult to use efficiently. A computer is adept at handling large amounts of data; and coupled with artificial intelligence techniques, one can actually train the computer into analyzing the stock market on its own. A computer can go beyond the limitations of the human brain by taking into consideration forgotten histories and chart patterns. The project aims at providing a market tracking system, one that will take into account three methods of analysis: fundamental and technical for long-term forecasting, as well as chaos modeling for short term predictions. The project is a tool, one that can help bring order and predictability to an otherwise random market.